The Orphan Seven-Transmembrane Receptor Apj Supports the Entry of Primary T-Cell-Line-Tropic and Dualtropic Human Immunodeficiency Virus Type 1 - Choe, Hyeryun (American Society for Microbiology, 1998)
Human immunodeficiency virus type 1 (HIV-1) enters target cells by sequential binding to CD4 and specific seven-transmembrane-segment (7TMS) coreceptors. Viruses use the chemokine receptor CCR5 as a coreceptor in the early, asymptomatic stages of HIV-1 infection but can adapt to the use of other receptors such as CXCR4 and CCR3 as the infection proceeds. Here we identify one such coreceptor, Apj, which supported the efficient entry of several primary T-cell-line tropic (T-tropic) and dualtropic HIV-1 isolates and the simian immunodeficiency virus SIVmac316. Another 7TMS protein, CCR9, supported the less efficient entry of one primary T-tropic isolate. mRNAs for both receptors were present in phytohemagglutinin- and interleukin-2-activated peripheral blood mononuclear cells. Apj and CCR9 share with other coreceptors for HIV-1 and SIV an N-terminal region rich in aromatic and acidic residues. These results highlight properties common to 7TMS proteins that can function as HIV-1 coreceptors, and they may contribute to an understanding of viral evolution in infected individuals.